Role of business sustainability, patriotism of business actors, and digital transformation in increasing MSME tax compliance - Pambayun Kinasih Yekti Nastiti; Theresia Woro Damayanti; Maria Rio Rita; Supramono Supramono (Cogent Business & Management)
This study aims to investigate the effects of digital transformation on business sustainability. The subsequent investigation will explore the impacts of business sustainability on tax compliance intentions, which are strengthened by the patriotism of business actors, particularly Micro, Small, and Medium Enterprise (MSME) actors. The sample for this study was taken from 360 culinary MSMEs across three cities in Indonesia: Semarang, Salatiga, and Surakarta, selected using a purposive sampling technique. The data was collected through a field survey approach and then analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS). The results reveal that digital transformation is demonstrated to have a significant impact on business sustainability. Furthermore, business sustainability has a significant outcome on tax compliance intentions. This study also finds that the patriotism of business actors is proven to strengthen the positive effects of business sustainability on tax compliance intentions. This study underscores the necessity for MSMEs to be encouraged to manage their businesses by prioritizing sustainable principles, particularly concerning their tax compliance intentions.